2022
DOI: 10.3390/ma15072684
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Technological Characterization of Zeolites from Basin and Range as Pozzolanic Addition of Cement

Abstract: The present paper assesses petrographic, mineralogical, chemical, and technological features of different zeolitic tuff samples from various western USA districts of the Basin and Range Province containing mainly erionite, mordenite, clinoptilolite/heulandite and phillipsite. The aim of this characterization is to evaluate the pozzolanic activity of these samples according to European normative UNI-EN 196/5 (Fratini test) to program a possible use as addition for blended cements. Petrographic and mineralogical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, after alginate coating, calcium deposition increased in both 7 and 14 days. Similarly, various studies [68][69][70][71][72][73][74][75][76][77][78][79][80] reported that alginate coating increased calcium deposition and new bone formation. For example, Jang et al [69] demonstrated the great calcium deposition results on the PCL scaffold with alginate coating.…”
Section: In Vitro Cytocompatibility Of Scaffoldsmentioning
confidence: 91%
“…In addition, after alginate coating, calcium deposition increased in both 7 and 14 days. Similarly, various studies [68][69][70][71][72][73][74][75][76][77][78][79][80] reported that alginate coating increased calcium deposition and new bone formation. For example, Jang et al [69] demonstrated the great calcium deposition results on the PCL scaffold with alginate coating.…”
Section: In Vitro Cytocompatibility Of Scaffoldsmentioning
confidence: 91%
“…Costafreda et al [20] and Costafreda [21] detailed in their previous research the pozzolanic characteristics of the zeolite of the Loma Blanca deposit, which were demonstrated once again in this work. Works such as those of Montesano et al [22], Uhlík et al [23], and Mertensa et al [24] established well the pozzolanic reactivity of zeolitised tuffs consisting mainly of mordenite and clinoptilolite.…”
Section: Chemical Analysis Of Pozzolanicity (Pt) At 8 and 15 Daysmentioning
confidence: 98%
“…According to [28], the first activity phases of the continental Phlegraean Fields correspond to Punta Marmolite and Cuma lava domes (~47 and ~37 ka, respectively), Torre Franco Tuff Formation (~42 ka) and San Martino lava dome (~77 ka). The two main eruptive events date back to ~39 ka ( 40 Ar/ 39 Ar; [28,29] and ~15 ka ( 40 Ar/ 39 Ar; [3]). The former is represented by the Campanian Ignimbrite eruption, the most catastrophic explosive event of the Mediterranean area in the last 200 ka, the latter is represented by the eruption of Neapolitan Yellow Tuff, the most impressive event of the Phlegraean Fields in terms of thickness and areal distribution [30].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…These geomaterials are particularly interesting due to their great use in the Roman age. Roman craftsmen used to combine lime and pozzolana, (formerly Pulvis Puteolana, volcanic sand from Pozzuoli, Italy) related to Neapolitan Yellow Tuff (NYT-15 ka) formation [2,3].…”
Section: Introductionmentioning
confidence: 99%